Values of Tri Hita Karana’s Palemahan in Roald Dahl’s The Twits - Kadek Agina Purwanita; Ni Komang Arie Suwastini; Ni Wayan Surya Mahayanti; I Nyoman Pasek Hadisaputra; I Putu Ngurah Wage Myartawan (STKIP AGAMA HINDU SINGARAJA, 2025)
One of the impacts of globalization is the amount of waste that damages the environment. One of the Balinese local wisdoms that can serve as a guideline for protecting the environment is the concept of Palemahan. In some studies, the value of Palemahan has been shown to enhance students' environmental care attitudes. To make it more interesting, Palemahan can be taught through novels. This study analyses the internalisation of Palemahan values reflected in the non-human protagonist characters in the book The Twits by Roald Dahl. Using the qualitative approach of Miles, et al., (2014), this study identifies how animals, such as the Muggle-Wump monkey and birds, practice key aspects of Palemahan values. The results showed that Roly Poly implemented the value of helping other animals four times, educating other animals once, and collaborating with other animals twice. At the same time, the Muggle Wump character embodies Palemahan values by longing for a harmonious habitat, showing sympathy for other animals, and occasionally helping them. This study found that The Twits contains Palemahan values that students can learn. This education guides teachers to integrate Palemahan local wisdom values through the novel The Twits, aiming to improve students' environmental awareness and develop innovative, relevant teaching materials.